INFLUENCE OF RAINFALL ENERGY AND OVERLAND FLOW ON SOIL LOSS FROM TERRACED PLANTATION ON STEEP TERRAIN OF DOI ANGKHANG PROJECT, CHIANG MAI - Tangtham, Nipon (วารสารวนศาสตร์ไทย, 2022)
The influence of rainfall energy and overland flow on soil loss within a plantation of 6 exotic tree species from Taiwan, planted with narrow terracing on steep terrain was determined. Data were collected from 4 x 15 m, runoff plots 2, 3 and 7 years after the plantation were established. One hundred and seventy six storm events of rainfall, runoff and soil loss from each of the tree-covered plots were incorporated in to this study. A linear regression relationship between storm rainfall and rainfall energy (Rs or El30 index) was found to be highly correlated with R2 ranges from 0.86 to 0.99. Narrow-bench terraces helped to reduce overland flow and led to a low correlation between soil loss and surface runoff. R2 which indicates the influence of surface flow on soil loss was less than 0.5 in all plantation plots in year 2 and 3, however, it was 0.92 in the bare plot. A very small R2 was obtained when Rs was added in the analysis. It can be concluded that narrow-bench terracing and the vegetation recovery greatly reduced both rainfall and runoff energy on the steep terrain.